Quantitative evaluation of empirical models of vortex-induced vibration of bridge decks through sectional model wind tunnel testing. (15th September 2020) - Xu, Kun; Ge, Yaojun; Zhao, Lin
Highlights: Bridge VIV system with different Scruton numbers are simulated in wind tunnel. Instantaneous properties of aeroelastic damping and stiffness are obtained. A method to obtain periodic equivalent damping of VIV models is proposed. Capabilities of commonly used VIV models are examined. Abstract: The capabilities of some commonly used single-degree-of-freedom (SDOF) VIV models for bridge decks are examined through wind tunnel experiment. The VIV responses of a sectional deck model at different Scruton numbers are measured. An instantaneous identification method is adopted for obtaining the properties of aeroelastic damping and stiffness of the VIV system. The simulated aeroelastic damping by these models as well as the predicted VIV responses of the deck at different Scruton numbers are compared with experiments. The results indicate that the more accurate the simulated aeroelastic damping by an empirical model, the smaller the prediction errors by this model will be. Through directly fitting the aeroelastic damping, the prediction errors by an empirical model can be further reduced.